Hematological profile and martial status in rugby players during whole body cryostimulation - Lombardi, G.; Lanteri, P.; Porcelli, S.; Mauri, C.; Colombini, A.; Grasso, D.; Zani, V.; Bonomi, F. G.; Melegati, G.; Banfi, G. (2013)
Cold-based therapies are commonly applied to alleviate pain symptoms secondary to inflammatory diseases, but also to treat injuries or overuse, as done in sports rehabilitation. Whole body cryotherapy, a relatively new form of cold therapy, consists of short whole-body exposure to extremely cold air (-110°C to -140°C). Cryostimulation is gaining wider acceptance as an effective part of physical therapy to accelerate muscle recovery in rugby players. The aim of this study was to evaluate the effect of repeated cryostimulation sessions on the hematological profile and martial status markers in professional rugby players. Twenty-seven professional rugby players received 2 daily cryostimulation treatments for 7 consecutive days. Blood samples were collected before and after administration of the cryotherapic protocol and hematological profiles were obtained. No changes in the leukocyte count or composition were seen. There was a decrease in the values for erythrocytes, hematocrit, hemoglobin and mean corpuscular hemoglobin content, and an increase in mean corpuscular volume and red cell distribution width. Platelet count and mean volume remained unchanged. Serum transferrin and ferritin decreased, while soluble transferrin receptor increased. Serum iron and transferrin saturation were unchanged, as was reticulocyte count, whereas the immature reticulocyte fraction decreased substantially. In conclusion, in this sample of professional rugby players, cryostimulation modified the hematological profile, with a reduction in erythrocyte count and hemoglobinization paralleled by a change in martial status markers.